Contactless In-Bed Movement in Various Scales Classification with CW Radar - Lu, Hui; Wenzel, Marvin; Steigleder, Tobias; Klinger, Isabell; Ostgathe, Christoph; Koelpin, Alexander (20th European Radar Conference, EuRAD 2023, 2023)
Continuous wave (CW) radar has been used to detect motions in various scenarios. In this paper, we first present a data-driven method to classify in-bed movement from various scales with CW radar. Data augmentation techniques are used to address the small sample size problem, resulting in a significant improvement of over 10% in accuracy. Three machine learning classifiers, namely random forest, k-nearest neighbor (k-NN), and multilayer perceptron (MLP), are evaluated, with random forest demonstrating the highest accuracy of 81.94% and relative improvement of 22.5% compared to k-NN. The movement sitting up from the bed can be classified with 97.5% accuracy. Additionally, the method can classify two types of movements involving only arm and leg movements, which are not visible to the radar, by detecting small-scale joint movements from the back with an accuracy of 74.8%.
CRIS-Team Scopus Importer:2023-12-01
Keywords: continuous wave radar; data augmentation; feature selection; machine learning; movement classification